Zoning of Historic Area in Pol Song Kram Sub-district Nonsung District, Nakhonratchasima Province - Usaad, Nantaporn (Academic MCU Buriram Journal, 2016)
The research objective of this research is to study changes of land use in Historic area in Prang Pol Song Kram Pol Song Kram Sub-district Non Sung district,Nakhonratchasima Province from years 1997 to 2015 and create map zoning of Historic area in Prang Pol Song Kram. Landsat 7 ETM+ and Landsat 8 OLI/TIRS imageries were chosen for the land use visualization with supervised classification process and analysis landuse change data. The result from research reveals changes of land use in Pol Song Kram Sub-district Non Sung district,Nakhonratchasima Province 1997 to 2015 that the total changed area is 49.56 Sq.Km. (73.84 %). The most proportion of changed decrease area is forest land And. the most proportion of changed increase area is agriculture land. Moreover, That found distribution of urban and built-up land around Historic area in Prang Pol Song Kram because of people don’t know how far they can stay from Historic area. It’s inconsistent of guidelines from Fine Arts Department. And Thus, the data should be accepted to play a better role to zoning of Historic area and environment management.